Current status of subclinical form of babesiosis and anaplasmosis in cattle at Rangpur district in Bangladesh (Progressive Agriculture, 2015)
Babesiosis and anaplasmosis are important tick borne diseases and they are responsible for significant economic losses for livestock industry worldwide. A cross-sectional survey was conducted in randomly selected 400 cattle at two upazilas of Rangpur district in Bangladesh, to estimate the prevalence and identify the risk factors of Babesia and Anaplasma infections. Microscopic examination of Giemsas stained blood films was carried out for the tentative diagnosis of infections. Multiplex PCR was also performed to confirm microscopically positive samples. To identify the risk factors, odds ratio and 95% confidence interval were calculated. The overall prevalence of Babesia and Anaplasma infections were 1.5% and 3.5%, respectively. The prevalence of Babesia infections recorded in Gangachara and Pirgachaupazilas were 1.3% and 1.7%, respectively while it was 3.8% and 3.3%, respectively for Anaplasma infection. Insignificantly higher prevalence of both infections was recorded in crossbred cattle than those of indigenous cattle. Female cattle had insignificantly higher infection (3.8%) with Anaplasma than the male cattle (2.3%) while no infection with Babesia was found in any male cattle. None of the calves (?1 yr) had infection with either organism. However, infection with both organisms was more prevalent in young cattle (>1-2.5 yr) than those of adult cattle (>2.5 yr). The availability of blood sucking ticks was one of the potential risk factors for both infections (OR = 6-7). Age (>1-2.5 yr) was identified as another important risk factor which had significant association with the occurrence of Anaplasma infection (OR = 4.36). The information generated from this study could be useful as basic information for further advanced epidemiological study and formulation of control measures of the tick borne diseases.Progressive Agriculture 26:51-59, 2015